THE PEDAGOGICAL CONDITIONS OF THE FORMATION OF DIGITAL COMPETENCE OF FUTURE LAW ENFORCEMENT OFFICERS IN THE PROCESS OF PROFESSIONAL TRAINING - Коченко, Ігор (SWorldJournal, 2022)
Features and advantages of the pedagogical conditions are highlighted. The general requirements of the professional training for using the pedagogical conditions for the formation of digital competence are given. The logic of developing, implementing, an